The Rehabilitation of the Philippines’ Bureau of Science Building in the Post-War Period, 1945-1958 - Maullon, Vince Elic S. (Diliman Review, 2021)
The Bureau of Science in Manila was the Philippines’ foremost scientific research and development facility during the American occupation period. Its work toward attaining scientific progress in the fledgling nation screeched to a halt in the wake of World War II, which culminated in the destruction of the buildings housing the Bureau, taking with its demise some forty years’ worth of invaluable scientific research, collections, and specimens. This paper aims to provide a comprehensive account of the events concerning the fate of the Bureau during the Battle of Manila and its post-war rehabilitation. Further, this paper posits that the Bureau’s prewar structure, largely presumed by historians and literature to have been lost in the War, was not entirely destroyed and was in fact rehabilitated and rebuilt in the same site as the original. This newer structure showcased a simpler architectural style and was rebuilt under the supervision of prominent state architect Federico Ilustre. However, despite these rehabilitative efforts, circumstances surrounding the building’s reconstruction in the post-colonial era contributed to the gradual erasure of the building’s relevance and significance from the Filipino collective memory and cultural milieu, leaving its legacy in relative obscurity. Keywords: Bureau of Science, World War II, science and technology in the Philippines, Federico Ilustre, collective memory